A conceptual framework for a multidimensional model of talent management data warehouse - Azwa, Abdul Aziz; Julaily Aida, Jusoh; Raja Hasyifah, Raja Bongsu (Asian Research Publishing Network, 2015)
The modern business environment and dynamic economic situation has made the workforce and business ethics more versatile and sophisticated. This development forges a complex business atmosphere that compels industries to compete productively for sustainable growth. Thus, it becomes imperative for organizations to manage their talents (workforce) effectively to achieve sustenance in the modern economic climate. Regrettably, it has been challenging for HR managers to identify, select and retain competent individual’s that suits their industrial needs (talent management). Therefore, this paper proposes a conceptual framework for a Multidimensional Model of a Data Warehouse (DW) for Talent Management (TM). Further, a hybrid approach of multidimensional modeling will be adopted in developing the model of the DW. In addition, student personal information and academic performances from institute of higher learning across Malaysia will be used as the data sources. Similarly, industrial needs (job vacancies) outlined by Multimedia Development Corporation (MDEC) Malaysia will be considered as user requirement. The proposed DW will provide information that will facilitate direct mapping of candidate to industrial needs among other TM practices. Also, the DW will facilitate various TM related analytics using appropriate Business Intelligence tool.